Acid-treated waste red mud as an efficient catalyst for catalytic fast copyrolysis of lignin and polyproylene and ozone-catalytic conversion of toluene - Ryu, Sumin; Lee, Jechan; Kannapu, Hari Prasad Reddy; Jang, Seong-Ho; Kim, Yeonjoon; Jang, Hoyeon; Ha, Jeong-Myeong; Jung, Sang-Chul; Park, Young-Kwon (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2020)
In this study, red mud (RM), a highly alkaline waste generated from alumina production industries, was used as a catalytic material for both fast copyrolysis of organosolv lignin (OL) and polypropylene (PP) and toluene removal under ozone at room temperature. The RM was pretreated with HCl to investigate the effect of alkalinity. In the catalytic fast copyrolysis of the OL and PP, the acid-treated RM (HRM) produced more aromatics, phenolics, and light olefins (C-3 to C-5) but less oxygenates and heavy olefins (C-6 to C-46) than the RM. The difference in pyrolytic performance between the RM and HRM was likely attributed to the concentrated Fe2O3 species in the HRM catalyst. In addition, more efficient toluene removal was observed over MnOx/HRM than over MnOx/RM owing to the large Brunauer-Emmett-Teller surface area, high amounts of Al and Fe, and optimal Mn3+/Mn4+ ratio. This study demonstrates that the RM, an industrial waste, can be reused as an effective catalytic material for not only biofuel production but also pollutant removal.
Keywords: CO-PYROLYSIS; LIGNOCELLULOSIC BIOMASS; DENSITY POLYETHYLENE; BAYER PROCESS; BIO-OIL; OXIDATION; DECOMPOSITION; MANGANESE; METAL; DECOLORIZATION